2014
DOI: 10.1093/gerona/glu137
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into SIRT1 Protection Against UVB-Induced Skin Fibroblast Senescence by Suppression of Oxidative Stress and p53 Acetylation

Abstract: Stresses, such as exposure to ultraviolet radiation and those associated with aging, are known to cause premature cellular senescence that is characterized by growth arrest and morphological and gene expression changes. This study was designed to investigate the protective effect of Sirtuin1 (SIRT1) on the UVB-induced premature senescence. Under in vitro experimental conditions, exposure to a subcytotoxic dose of UVB enhanced human skin fibroblasts senescence, as characterized by increased β-galactosidase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…Thus, SIRT1 may regulate p53 function by deacetylating p53. Chung et al reported that the overexpression of SIRT1 significantly protects fibroblasts from UVB-induced cellular senescence by suppressing UVB-induced p53 acetylation and its transcriptional activity (35). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, SIRT1 may regulate p53 function by deacetylating p53. Chung et al reported that the overexpression of SIRT1 significantly protects fibroblasts from UVB-induced cellular senescence by suppressing UVB-induced p53 acetylation and its transcriptional activity (35). …”
Section: Discussionmentioning
confidence: 99%
“…Because p53 is deacetylated by SIRT1 the Acp53/p53 ratio was used to assess the activity of SIRT1 (Chung et al 2015;Feng et al 2015;Kim et al 2016;Li et al 2015;Song et al 2015;Weidele et al 2017) and the results showed that exercise and NAM treatment as well as the combined effects of these increased the activity of SIRT1 in old muscle. In terms of exercise training this is similar to our earlier results (Koltai et al 2010(Koltai et al , 2012 however, the intensity of training was much less than that used in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse double minute 2 homolog ( Mdm2 ) and the E3 ubiquitin-protein ligase are important negative autoregulators of p53. MDM2 binds to FOXO1 and FOXO3A and promotes their ubiquitination and subsequent degradation (Chung et al, 2015[13]; Fu et al, 2009[21]; Huang and Tindall, 2011[25]). The Wnt/β-catenin pathway regulates FOXO1 activities.…”
Section: Introductionmentioning
confidence: 99%